Assessment of Science Teachers' Awareness towards Communicable Diseases Control in Baghdad City Primary Schools - Faraj, raad; Khalifa, mohammed (Iraqi National Journal of Nursing Specialties, 2014)
Objective: To assess of Science Teachers' Awareness towards Communicable Diseases Control in Baghdad CityPrimary SchoolsMethodology: A descriptive study was conducted, included (100) primary school, (50) in Al-Rassafa sector, and(50) in Al-Karkh sector, from March 5th 2012 to March 15th 2013, to assess of science teachers' awarenesstowards communicable diseases control. A cluster sample of (100) Science teachers (males and females) wereselected, as one teacher from each school. A questionnaire format was used for data collection. The validity ofquestionnaire was estimated through a penal of experts related to the field of study, and its reliability wasestimated through a pilot study conducted in (20) schools (excluded from the original sample) which included (20)teachers from April 8th 2012 to April 14th 2012. Data were analyzed through the application of descriptive andinferential statistical analysis.Results: The results of the study indicated that (78%) of sample were female, and (39%) of them their ages werebetween (40-49) years old, (65%) of them were married, while (21%) of them were single, and (50%) of them wereinstitute graduates. Also the study indicated that (26%) of teachers had (15–19) years of employment in teachingsector. Furthermore, (58 %) of sample had no opportunity to be involved in training courses concerningcommunicable diseases control. The results of this study indicate that, teachers' awareness was poor (in adequateawareness) towards communicable diseases control, immunity and immunization, and also concerning healthproblems in school.Recommendations: The study recommends that there is a need for cooperation between the Ministry of Healthand the Ministry of Education to prepare a textbook for primary schools students about the nature of thecommunicable diseases and how to control them with adequate explanation of the most important diseases inschool provided with photos and illustrations, and emphasis on continuous sessions concerning communicablediseases control for teachers in all primary schools